2022
DOI: 10.3892/ijo.2022.5440
|View full text |Cite
|
Sign up to set email alerts
|

PD‑L1 mediates triple‑negative breast cancer evolution via the regulation of TAM/M2 polarization

Abstract: Tumor-associated macrophages/M2-type (TAM/M2) play a key role in the metastasis and angiogenesis of cancer, and are considered to be critical targets for cancer treatment. However, it remains unclear whether α-programmed death-ligand 1 (αPD-L1; PD-L1 inhibitor) inhibits tumor progression via targeting TAMs. In the present study, it was demonstrated that αPD-L1 significantly inhibited IL-13-induced TAM/M2 polarization in vitro. Moreover, αPD-L1 inhibited the epithelial-mesenchymal transition (EMT) process and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 51 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…In addition, TAMs are involved in crosstalk with CSCs in various types of tumors 61 . M2-type TAMs promote cancer stem-like properties in tumors, including hepatocellular carcinoma 62 , breast cancer 63 , non-small cell lung cancer 64 , pancreatic ductal adenocarcinoma 65 , and glioblastoma multiforme 66 . Mitchum et al showed that ablation of CCR2 or CSF-1R signaling significantly blocked TAM infiltration in pancreatic ductal adenocarcinoma (PDAC), reduced the number of CD44 + ALDH1 + CSCs, and improved the response to chemotherapy 67 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TAMs are involved in crosstalk with CSCs in various types of tumors 61 . M2-type TAMs promote cancer stem-like properties in tumors, including hepatocellular carcinoma 62 , breast cancer 63 , non-small cell lung cancer 64 , pancreatic ductal adenocarcinoma 65 , and glioblastoma multiforme 66 . Mitchum et al showed that ablation of CCR2 or CSF-1R signaling significantly blocked TAM infiltration in pancreatic ductal adenocarcinoma (PDAC), reduced the number of CD44 + ALDH1 + CSCs, and improved the response to chemotherapy 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Tumors overexpressing PD-L1 are often accompanied by the infiltration of PD-1-positive TILs, which are associated with shortened overall survival, indicating a poor prognosis for breast cancer (Muenst et al 2013 ; Sun et al 2014 ). PD-L1 affects not only T cells but also tumor-associated macrophages, inducing tumor-promoting M2 polarization (Meng et al 2022 ; Zhang R et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…TAMs mainly refer to M2-type macrophages, which form an immunosuppressive microenvironment and promote tumor growth and angiogenesis through cytokine production. 79 , 80 As a bridge between innate and adaptive immunity, DCs play a significant role in antigen presentation. 81 It can be seen that immune cells in the TME cannot act alone, and interactions between immune cells may lead to reconstruction of the TME and thus promote or inhibit tumor processes.…”
Section: Application Of Translationomics For Immune Cells In the Tumo...mentioning
confidence: 99%